2018
DOI: 10.1155/2018/3023096
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Sinus Lift Using Autologous Periosteal Micrografts: A New Regenerative Approach and a Case Report of a 3-Year Follow-Up

Abstract: This case report discusses about an innovative bone regeneration method that involves the use of autologous periosteal micrografts, which were used for a maxillary sinus floor lift in a 52-year-old female patient. This method allows for harvesting of a graft that is to be seeded on a PLGA scaffold and involves collection of a very little amount of palatal periosteal tissue in the same surgical site after elevation of a flap and disaggregation of it by using a Rigenera® filter. Histological samples collected at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…From Brånemark's initial studies, titanium represents the most-used material, although not the only one, for the production of endosseous dental implants [1][2][3]. Success rates with titanium implants are high in both the short and long term; moreover, they are indicated in many particular situations [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…From Brånemark's initial studies, titanium represents the most-used material, although not the only one, for the production of endosseous dental implants [1][2][3]. Success rates with titanium implants are high in both the short and long term; moreover, they are indicated in many particular situations [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…At 12 months, the mean radiographic bone fill levels were 3.9 ± 1.5 mm and 1.6 ± 1.1 mm in the test and control groups, respectively. Regarding sinus lift, in a retrospective study [18], radiological follow-up at 4 months showed greater mineralization in the group treated with a micrograft combined with hydroxyapatite than in the two control groups in which hydroxyapatite or deproteinized bovine bone was used alone. Histological and histomorphometric data showed a statistically significant result, with more vital mineralized tissue (p<0.004) in the group treated with combined micrograft/hydroxyapatite (58.5 ± 2.5% with respect to the control group) than in those treated with hydroxyapatite (20.2 ± 3.1%) or deproteinized bovine bone alone (48 ± 2.5%), and more non-mineralized tissue (p < 0.003) in the group treated with combined micrograft/hydroxyapatite (41.4 ± 5.6%) than in those treated with hydroxyapatite (5.5 ± 1.6%) or deproteinized bovine bone alone (20.5 ± 3.1%).…”
Section: Resultsmentioning
confidence: 97%
“…In the control group, a collagen sponge or hydroxyapatite alone was used (Table 3). Sinus augmentation with micrografts was described in a retrospective study [16] and in two case reports [17,18], whereas periodontal regeneration was assessed in a randomized clinical trial [19], a case series [20], and a case report [21]. Furthermore, two case series of socket preservation with test and control were published by d 'Aquino et al in 2009 [22] and 2016 [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though it was not necessary because randomization was implemented before surgery, the implant label choice for the sides of the mouth was randomized by a coin toss. The surgical protocol of installing the implants was well documented and consisted of a full thickness mucosal flap elevation, the preparation of the implant site, the installation of the implant with the prosthetic platform (that is, the edge of the collar) at the level of the bone crest, the positioning of the surgical cover screw, and the closing of the flap with sutures [73,74,75,76,77,78,79,80]. The surgery was done under coverage of antibiotics (2 g of amoxicillin and clavulanic acid per os one hour before surgery, followed by administration of 1 g after 6 and 18 h).…”
Section: Methodsmentioning
confidence: 99%